Level, pattern, and determinants of polypharmacy and inappropriate use of medications by village doctors in a rural area of Bangladesh - Rasu RS; Iqbal M; Hanifi SMA; Moula A; Hoque S; Rasheed S; Bhuiya A (Dove Medical Press, 2014)
Rafia S Rasu,1 Mohammad Iqbal,2 SMA Hanifi,2 Ariful Moula2 Shahidul Hoque,2 Sabrina Rasheed,2 Abbas Bhuiya2 1School of Pharmacy, University of Missouri-Kansas City, Kansas City, MO, USA; 2Centre for Equity and Health System, International Centre for Diarrhoeal Disease Research (ICDDR,B), Dhaka, Bangladesh Objective: Village doctors, informal health care providers practicing modern medicine, are dominant health care providers in rural Bangladesh. Given their role, it is important to examine their prescription pattern and inappropriate use of medication. Methods: These cross-sectional study data were collected through surveys of patients seen by village doctors during 2008 and 2010 at Chakaria, a typical rural area of Bangladesh. Categorization of appropriate, inappropriate, and harmful prescriptions by disease conditions was based on guidelines defined by the World Health Organization (WHO), the United Nations Children’s Fund (UNICEF), and the Government of Bangladesh. Analytical categorization of polypharmacy was defined when five or more medications were prescribed for a patient at a single visit. Findings: A total of 2,587 prescriptions were written by village doctors during the survey periods. Among the prescriptions were appropriate (10%), inappropriate (8%), combination of appropriate and inappropriate (63%), and harmful medications (19%). Village doctors with more than high school education were 53% less likely (odds ratio [OR]: 0.47, 95% confidence interval [CI]: 0.26–0.86) to give polypharmacy prescriptions than those with less than high school education. While exploring determinants of prescribing inappropriate and harmful medications, this study found that polypharmacy prescriptions were six times more likely [OR: 6.00, 95% CI: 3.88–9.29] to have harmful medications than prescriptions with <5 medications. Conclusion: Village doctors’ training and supervision may improve the quality of services and establish accountability for the benefit of the rural population. Keywords: Bangladesh, harmful medication, ICDDR,B, informal health care providers, polypharmacy, rural area, village doctors